Mental Resilience Optimization: A Screening and Educational Initiative Addressing Adolescent Hopelessness and Self-Harm Risks - Ekawati, Dessy; Maunaturrohmah, Agustina; Wijayanti, Anin; Nofalia, Ifa (Jurusan Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2026)
Adolescents frequently encounter complex emotional pressures that can lead to a profound sense of hopelessness, which is a primary precursor to non-suicidal self-injury behaviors. This community service initiative aimed to mitigate despair and enhance psychological literacy among eleventh-grade students at SMAN 2 Jombang through a systematic screening and educational intervention. The program involved 40 participants selected via purposive sampling who demonstrated moderate baseline hopelessness. The one-day intensive session incorporated multimedia tools, including structured presentation slides, an educational video, and a printing pocket module focusing on hope-building strategies and adaptive coping mechanism simulations. Evaluation was conducted using pre-intervention and post-intervention assessments through the standard Beck Hopelessness Scale (BHS; 20 items, scored 0–20) and a specialized self-harm risk awareness questionnaire. The latter was a pre-tested 15-item instrument utilizing a 4-point Likert scale (1 = Strongly Disagree to 4 = Strongly Agree) to measure students' understanding of maladaptive behaviors. Baseline results indicated that 17.5% of students exhibited severe hopelessness, while 72.5% were in the moderate category. Following the intervention, a substantial shift occurred where 70% of participants reached the minimal-to-mild hopelessness level, and only 5% remained in the severe category. Furthermore, students' understanding of self-harm risks improved significantly, with the very high awareness group increasing from 5% to 30%. This educational initiative proved effective in strengthening adolescent psychological resilience, establishing empirical baseline data for the institution. It is recommended as a sustainable, school-based strategy by integrating screening tools into the annual guidance curriculum for early crisis detection.